Diagnosis and Management of Atypical Chronic Myeloid Leukemia with a t(2;13)(q33;q12) Translocation - John S. Wang; Omar Elghawy; Brett R. Kurpiel; Michael G. Douvas (Case Reports in Hematology)
Atypical chronic myeloid leukemia (aCML) is a rare myeloproliferative disorder that shares clinical features with chronic myeloid leukemia but lacks the classic t(9;22) BCR-ABL1 translocation and features prominent dysgranulopoiesis and granulocytic dysplasia. Challenges of this diagnosis include clinical and biologic heterogeneity, the high risk of transformation to acute myeloid leukemia, and the lack of standard treatment options. Allogeneic hematopoietic stem cell transplant is likely the preferred treatment, but this can be limited by patient psychosocial support, age, concomitant medical conditions, and availability of an appropriate donor. We report the case of a 61-year-old male with no significant past medical history diagnosed with aCML with a rare t(2;13)(q33;q12). He presented with weight loss, night sweats, splenomegaly, hyperleukocytosis, a leukoerythroblastic differential with a predominant neutrophilia, anemia, and thrombocytopenia. Subsequent peripheral blood and bone marrow studies lead to the diagnosis of aCML. He was recommended to undergo an allogeneic stem cell transplant evaluation and declined. He was initially treated with hydroxyurea and imatinib to which he responded for approximately three years. After clinical progression, he was treated with sorafenib, a multiprotein kinase inhibitor more commonly used in the treatment of hepatocellular and renal cell carcinoma due to its off target FLT3 inhibition. The patient achieved complete hematologic response which has been sustained for 7 years with tolerable side effects.